The Relationship between Self-Management and Autonomous Learning of the Santri at Modern Pondok Pesantren of Al-Ikhlas Lubuklinggau - Budi Astuti; Andika Ari Saputra (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2020)
This study aims to determine: the relationship between self-management and autonomous learning of the santri at Pondok Pesantren Modern of Al-Ikhlas Lubuklinggau. This research is a correlation and ex post facto research. The research population comprised all 507 santri of Al-Ikhlas Lubuklinggau Modern Pondok Pesantren. A sample of 253 students was determined by a proportional stratified random sampling technique. The variables studied were self-management and autonomous learning. The data collection method uses a scale (inventory), the tool is in the form of self-management scale and scale of autonomous learning. A validity test is done with the help of a computer program SPSS 22 for windows. Reliability test using technique Cronbach's alpha, obtained p = 0.740 for self-management variables and p = 0.744 for learning independence variables. The analysis technique used is descriptive and inferential statistics with the SPSS 22 for windows program. The results showed that there was a relationship between self-management and students' self-learning independence of 0.864, a probability value of 5% Ts was 0.000 (p <0.05).